Clinical Observation on the Third-lumbar Transverse Process Syndrome Treated by Chiropractic Gun Combined with Pulse Edge Needle - Yuanyang ZHANG; CongShan CHEN; Xueping WU; Wen LIANG; Yu HUANG; Xiaoming RAO; Zhiwei QIU (康复学报)
Objective:To observe the clinical efficacy on the third-lumbar transverse process syndrome treated by chiropractic gun combined with pulse edge needle.Methods:One hundred cases of the third-lumbar transverse process syndrome were randomly divided into treatment group and control group, 50 cases in each group. The control group was treated by pulse edge needle, and the treatment group was treated by chiropractic gun combined with pulse edge needle. VAS score, the lumbar dysfunction score, ADL score and lumbar spine mobility were compared between the two groups before and after treatment, and after treatment were followed up in 2 weeks.Results:Compared with before treatment, VAS score and lumbar dysfunction score of the two groups treated after 2 weeks and 4 weeks were significantly decreased (P<0.05), while the treatment group decreased more than the control group (P<0.05). Compared with before treatment and the control group, ADL score and lumbar spine mobility of the treatment group were significantly increased (P<0.05),Conclusion:Chiropratic gun combined with pulse edge needle can obviously alleviate waist pain of the third-lumbar transverse process syndrome, improving the treatment effect and clinical application value.